2022: Are We Back to the pre-COVID-19 Pandemic Period in the Management of out-of-Hospital Cardiac Arrest? (Epidemiology, Biostatistics, and Public Health, 2023)
Introduction: The COVID-19 pandemic caused a significant strain on the Emergency system, particularly for time-dependent diseases like Out of Hospital Cardiac Arrest (OHCA). Studies have shown an increase in the incidence of OHCA during different waves of the pandemic, but there is limited evidence on how survival rates and rescue efforts have been affected in the post-pandemic period. Methods: We performed a retrospective observational cohort study of all OHCA rescues by AREU (Agenzia Regionale Emergenza Urgenza), in the Lombardy region in March in three different years (2019, 2021 and 2022). We used rescue mission data collected in AREU’s database, where logistic information of patient rescue missions managed by the Lombardy Region’s 112 system is recorded.Results: This study was an epidemiology analysis of OHCA after the pandemic. The results showed no significant changes in the probability of receiving bystander cardiopulmonary resuscitation (22.5% vs 24.0%; p=0.41) and public access defibrillation (3.6 vs 3.2; p=0.50) compared to pre-pandemic period. However, there was a decrease in the probability of ROSC (11.5% vs 6.2%; p
Keywords: Covid-19; Resuscitation; Out-of-Hospital cardiac arrest; Emergency Medical Service